2021
DOI: 10.2478/jeppm-2021-0011
|View full text |Cite
|
Sign up to set email alerts
|

Mediation Effect of Stakeholder Management between Stakeholder Characteristics and Project Performance

Abstract: Effective stakeholder management (ESM) is a critical success factor for projects. The increasing complexity in the relationships among stakeholders and their diverse characteristics, including power and interests makes the management of stakeholders increasingly challenging. To date, much of the literature has focused on the stakeholder analysis with very limited to the direct and indirect relationships between stakeholder characteristics (SC) and project performance (PP). Therefore, the aim of this study is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…The information flow between the project and stakeholders is no longer unidirectional but transformed into a dialogue that allows participants to take part in developing the project (Libaert, 1998). Accordingly, some scholars have suggested that to improve stakeholder engagement, the firms need to encourage stakeholder management strategies (Khan et al, 2017;Khan & Iqbal, 2019;Larsson & Larsson, 2020;Nguyen & Mohamed, 2021), enhance communication and collaboration with project stakeholders (Fraz et al, 2016), and promote stakeholder awareness initiatives (Khan et al, 2017;Saad et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The information flow between the project and stakeholders is no longer unidirectional but transformed into a dialogue that allows participants to take part in developing the project (Libaert, 1998). Accordingly, some scholars have suggested that to improve stakeholder engagement, the firms need to encourage stakeholder management strategies (Khan et al, 2017;Khan & Iqbal, 2019;Larsson & Larsson, 2020;Nguyen & Mohamed, 2021), enhance communication and collaboration with project stakeholders (Fraz et al, 2016), and promote stakeholder awareness initiatives (Khan et al, 2017;Saad et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…On the digital era, the possibility for collaboration is facilitated and co-creation is even more disseminated; therefore, the stakeholder engagement on projects is beneficial to achieve goals and success (Barrane et al, 2020). In technology projects, the dynamic and changes are even more pronounced since the innovation happens quickly and the project must adapt to constant changes; hence, the stakeholder engagement and register help managers to deal effectively with each participant and accomplish better responses (Nguyen and Mohamed, 2021).…”
Section: Stakeholder Managementmentioning
confidence: 99%
“…Other factors, such as disputes between key stakeholders, may account for project cost overrun (Yang et al , 2018). Nguyen and Mohamed (2020) discovered that conflicting stakeholder interests negatively affect both quantitative and qualitative PP. Quantitative PP included schedule and cost performance, whereas quantitative PP included the project’s quality, project scope and stakeholder satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative PP included schedule and cost performance, whereas quantitative PP included the project’s quality, project scope and stakeholder satisfaction. Nguyen and Mohamed (2020) revealed that effective stakeholder management could reduce the negative effect of conflicting stakeholder interests on PP. SE was identified as the main contributor to effective stakeholder management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation